VARIASI BAHASA MASYARAKAT KARO JAHE DI DESA NAMO MIRIK KECAMATAN KUTALIMBARU: KAJIAN SOSIOLINGUISTIK - Meriah Kita Barus; Yefta Vianus Marbun (Balai Bahasa Sumatera Utara, 2022)
People who use Karo language are divided into two, namely Karo Gugung and Karo Jahe. The use of language can be seen from the differences in vocabulary, sentence structure, and dialect. The aims of this study were (1) to describe the variations of the Karo Jahe language seen from the association of speakers and the function of the language used by the people of Namo Mirik Village, Kutalimbaru District and (2) the factors that cause language variations in the speaking community. The research method used is descriptive qualitative method. The research data is in the form of quotations of words, phrases, or conversational sentences used by the people of Namo Mirik Village, Kutalimbaru District. The data collection technique used is listen listen, get involved and talk (SLC). The results of the study found that (1) language variations from various social levels included the Karo Jahe dialect, the use of basilek, vulgar, slang, colloquial, and jargon languages. Meanwhile, language variation can be seen from the diversity of language functions in agriculture or in accordance with people's livelihoods and the use of language from a formal perspective, namely in the event of customs. (2) Factors that influence the occurrence of language variations in the people of Namo Mirik Village, Kutalimbaru District, include aspects of place, social status (education), situation (local customs), and profession.